PERSEPSI MAHASISWA TERHADAP AKAD SALAM PADA TRANSAKSI PEMESANAN MAKANAN MELALUI GOFOOD DENGAN PEMBAYARAN DIGITAL GOPAY (Studi Pada Mahasiswa Keuangan dan Perbankan Syariah Politeknik Negeri Medan) - Naila Anggraini; Hubbul Wathan; Gatot Teguh Arifyanto; Muhammad Zuhirsyan; Amrin Amrin (Smart Education, 2026)
Abstract: This study aims to examine the perceptions of students in the D4 Islamic Finance and Banking Study Program at Politeknik Negeri Medan regarding the implementation of the salam contract (akad salam) in food-ordering transactions through GoFood using GoPay digital payment, as well as the compliance of such transaction with the principles of fiqh muamalah. This study employes a qualitative method with a descriptive approach. Data were collected through interviews with 11 students selected using purposive sampling. The results indicate that students' perceptions of the implementation of the salam contract (akad salam) in GoFood transactions using GoPay were generally positive. Students understood that the transaction mechanism possesses the characteristics of a salam contract (akad salam) and considered it to be consistent with the principles of fiqh muamalah. Furthermore, GoFood transactions using GoPay were considered to fulfill the requirements of a salam contract (akad salam), including advance payment, clear product specifications, a clearly defined delivery time, mutual agreement between the parties, and delivery of the goods in accordance with the agreed order. Therefore, food ordering transactions through GoFood using GoPay digital payment are considered to comply with the provisions of the salam contract (akad salam) from the perspective of fiqh muamalah. Keywords: Student Perceptions, Salam Contract, Digital Transactions Abstrak: Penelitian ini bertujuan untuk mengetahui persepsi mahasiswa Program Studi D4 Keuangan dan Perbankan Syariah Politeknik Negeri Medan terhadap penerapan akad salam pada transaksi pemesanan makanan melalui GoFood dengan pembayaran digital GoPay serta kesesuaiannya dengan fiqh muamalah. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data diperoleh melalui wawancara terhadap 11 mahasiswa yang dipilih menggunakan teknik purposive sampling. Hasil penelitian menunjukkan bahwa persepsi mahasiswa terhadap penerapan akad salam pada transaksi GoFood dengan pembayaran GoPay cenderung positif. Mahasiswa memahami bahwa mekanisme transaksi tersebut memiliki karakteristik akad salam dan menilai telah sesuai dengan prinsip fiqh muamalah. Selain itu, transaksi GoFood dengan pembayaran GoPay dinilai telah memenuhi ketentuan akad salam, yaitu pembayaran di muka, kejelasan spesifikasi barang, kejelasan waktu penyerahan, kesepakatan para pihak, serta penyerahan barang sesuai pesanan. Dengan demikian, transaksi pemesanan makanan melalui GoFood dengan pembayaran digital GoPay telah sesuai dengan ketentuan akad salam dalam perspektif fiqh muamalah. Kata kunci: Persepsi Mahasiswa, Akad Salam, Transaksi Digital